2017
DOI: 10.22603/ssrr.1.2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of instrumentation failure after multilevel total en bloc spondylectomy

Abstract: Abstract:Introduction: Multilevel total en bloc spondylectomy (TES) is required to secure oncologically adequate resection margins. However, no useful information has been reported for spinal reconstruction after multilevel TES. Therefore, this study set out to assess the clinical and radiological outcomes of spinal reconstruction after multilevel TES. Methods: Forty-eight patients treated with multilevel TES at our institute were included in the analysis. Reconstruction was achieved with posterior pedicle scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 38 publications
2
47
0
Order By: Relevance
“…The previously reported incidence rate of instrumentation failure after TES using the same reconstruction method as ours (except using fresh autologous bone for bone grafting) was 17.0% (8/47) [11]; in the present study, the instrumentation failure rate after TES using frozen bone was 42.6% (26/61). It was reported that bone formation tended to be delayed when frozen bone autografts were used compared with fresh bone autografts [25]; therefore, the instrumentation failure rate in the present study was higher than that previously reported [11]. Although bone fusion was delayed, complete bone fusion within the cage was obtained in the TES model canine using frozen bone [25].…”
Section: Discussionsupporting
confidence: 69%
“…The previously reported incidence rate of instrumentation failure after TES using the same reconstruction method as ours (except using fresh autologous bone for bone grafting) was 17.0% (8/47) [11]; in the present study, the instrumentation failure rate after TES using frozen bone was 42.6% (26/61). It was reported that bone formation tended to be delayed when frozen bone autografts were used compared with fresh bone autografts [25]; therefore, the instrumentation failure rate in the present study was higher than that previously reported [11]. Although bone fusion was delayed, complete bone fusion within the cage was obtained in the TES model canine using frozen bone [25].…”
Section: Discussionsupporting
confidence: 69%
“…A biomechanical study demonstrated that multi-segmental posterior xation with anterior column reconstruction can provide better stability than short xation and that xation should be extended to 2 ~ 3 levels above and below the resected vertebrae [23]. However, instrumentation failure, the incidence of which varies from 17.0-40%, is not a rare complication following a long-segment xation procedure after TES [7,13,24,25]. Among the types of IF, such as screw loosening, screw backout, cage breakage, screw fracture, and rod breakage, rod fracture is the most common and often leads to a high reoperation rate due to aggravating back pain or neurologic deterioration [9,24].…”
Section: Discussionmentioning
confidence: 99%
“…Among the types of IF, such as screw loosening, screw backout, cage breakage, screw fracture, and rod breakage, rod fracture is the most common and often leads to a high reoperation rate due to aggravating back pain or neurologic deterioration [9,24]. Cage subsidence, a history of radiotherapy, and a low spinal level of involvement have been con rmed to be risk factors related to rod fracture [7,9,24,25]. The survival time of spinal tumor patients is longer when primary tumors and metastatic tumors are resolved, so reconstruction of the three columns of the spine with additional posterior column reconstruction is very important [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A biomechanical study demonstrated that multi-segmental posterior xation with anterior column reconstruction can provide better stability than short xation and that xation should be extended to 2~3 levels above and below the resected vertebrae [23]. However, instrumentation failure, the incidence of which varies from 17.0% to 40%, is not a rare complication following a long-segment xation procedure after TES [7,13,28,29]. Among the types of IF, such as screw loosening, screw back-out, cage breakage, screw fracture, and rod breakage, rod fracture is the most common and often leads to a high reoperation rate due to aggravating back pain or neurologic deterioration [9,28].…”
Section: Discussionmentioning
confidence: 99%